Age-composition of mature area under natural rubber in India: A comparative analysis - Jacob Jom; George K T (Rubber Science, 2016)
The paper revisits a study undertaken by the authors in 2008 on the trends in age-composition of mature area under natural rubber cultivation in India and reviews projected status for the period from 2008-09 to 2014-15. The projections of the earlier study showed that the share of area under the yield-declining phase would rise to touch 53.3 per cent by 2011-12 before falling to 46.0 per cent by 2014-15. The earlier study had also highlighted inconsistencies in the official data and recommended a national census of rubber area for fixing the same. However, the earlier study failed to capture the postponement of the uprooting of rubber trees beyond 22 years of tapping age and the resultant emergence of a senile group of trees having more than 22 years of tapping age. Due to retention of aged trees, the gap between the projected figures of mature area and the corresponding official figures sharply widened from 2.2 per cent in 2008-09 to 25.3 per cent in 2014-15. The area occupied by trees having more than 22 years of tapping age steadily grew by 144.7 per cent during the period from 2008-09 to 2014-15. In absolute terms, the area under theis age-group increased from 10,255 hectare to 99,313 hectare with important policy implications. The results of the study reconfirmed the need for a national census of rubber area, as proposed in the earlier study.
Keywords: Age-composition; Average yield; Census; New-planting; Replanting; Tapping age